Potensial Antimalaria dan Antioxidan Ekstrak Metanol Daun kayu titi (Alstonia sp) - Maria Nindatu; Matha Kaihena; Adriana Hieriej; Amos Killay; Hery Jotlely (Jurnal Penelitian Pendidikan IPA, 2023)
Alstonia sp leaves extract has previously been reported as a potential antimalarial drug as traditional. This study aims to analyze the antimalarial activity and determine the antioxidant potential of titi tree leaves (Alstonia sp). The method used in this research is a modified method of "4 Days Suppressive Test" which was originally described by Peter with different doses (0.55 g/kg, 0.65 g/kg and 0.75 g/kg body weight) of methanol extract of leaves of Titi tree (Alstonia sp) was administered orally to albino mice. Antioxidants were analyzed using a spectrophotometer. The Leaves of Alstonia sp has antimalarial activity and contains potential antioxidant activity with an IC50 value of 70.12 ppm for leaves (strong category). The dose of 0.75 g has a better effect compared to the other effects because it lowers the level of parasitemia more strongly. So that the leaves of Alstonia sp. pressured to be developed as a nutraceutical.